Is China's Regional Economy Converging or Diverging? : - Kong, Decong (2023)
Since implementing economic reforms and opening up policies, China has experienced a significant disparity in economic development across its regions. While the gaps in regional economic growth have narrowed to some extent, there are still significant differences between regions. Various factors, including local government strategies, geographical locations, infrastructure, and market conditions, contribute to these regional disparities. This Master thesis aims to comprehensively examine and analyze the factors that contribute to these disparities in China's regional economy. By analyzing time series data spanning the past 20 years and incorporating indicators such as GDP per capita, infrastructure, and international trade statistics, this research delves into different Chinese regions, through a systematic analysis of each region's unique economic circumstances. By optimizing the model for specific regions, the study seeks to identify the key factors driving regional economic differences. Additionally, it seeks to measure and predict whether these regions will experience convergence or divergence in their future economic trends using specific indicators.